Manajemen Sarana dan Prasarana dalam Meningkatkan Efektivitas Pembelajaran - Ona Wanty Kune; Junilda Tefbana; Mersi Liu; Soleman Teflaka; Steven H. C Selan; Yanti Y. E. Sole (Jurnal Ilmiah Literasi Indonesia, 2026)
This research seeks to delineate and examine the execution of facilities and infrastructure management and its contribution to enhancing the efficacy of learning in educational institutions. This research uses a qualitative approach via a literature review. The literature study approach, or library research, entails gathering data and information via the examination of textual sources, including scientific journals, reference books, and other credible materials, in both print and digital media, pertinent to the subject of investigation. Research participants include school administrators and instructors. The data were analysed use the model proposed by Miles and colleagues, which encompasses the steps of data reduction, data presentation, and conclusion formulation. The findings indicate that facilities and infrastructure management, including planning, procurement, utilisation, maintenance, and inventory, is crucial for establishing an effective learning environment. Effective management has been shown to enhance learning efficacy, including both academic performance and character development of students. The primary obstacles encountered consist of financial limitations, inadequate regular maintenance, and a deficient inventory system necessitating improvement. This research suggests that organised, well-maintained, and methodical facility management is a critical aspect for the overall effectiveness of the educational process